Cardiac tamponade caused by metastasising haemangioendothelial sarcoma of the liver. Issue 6 (June 1978) - Syed, S; Jung, R T
Abstract : A case of primary haemangiosarcoma of the liver with secondary deposits in the pericardium is described. The patient presented most unusually with cardiac tamponade. There was no association with vinyl chloride, thorium dioxide, or arsenic.